Cetacean Morbillivirus-Associated Pathology: Knowns and Unknowns - Di Guardo, Giovanni; Mazzariol, Sandro (Frontiers in Microbiology, 2016)
The present minireview deals with the pathology of Cetacean Morbillivirus (CeMV) infection in free-ranging cetaceans. In this respect, while “classical” CeMV-associated lesions were observed in the lung, brain and lymphoid tissues from striped dolphins (Stenella coeruleoalba) and pilot whales (Globicephala melas) which were victims of the 1990-’92 and 2006-’08 epidemics in the Western Mediterranean, an apparent reduction in CeMV neurovirulence, along with a different viral antigen’s tissue and cell distribution, were found during the 2010-’11 and the 2013 outbreaks in the same area. Of remarkable concern are also the documented CeMV ability to induce maternally acquired infections in wild cetaceans, coupled with the progressively expanding geographic and host range of the virus in both Hemispheres, as well as in conjunction with the intriguing forms of “brain-only” morbilliviral infection increasingly reported in Mediterranean striped dolphins. Future research in this area should address the virus-host interaction dynamics, with particular emphasis on the cell receptors specifying viral tissue tropism in relation to the different cetacean species and to their susceptibility to infection, as well as to the CeMV strains circulating worldwide.